Removing of Direct Red 83:1 using α- and HP-α-CDs polymerized with epichlorohydrin: Kinetic and equilibrium studies. (February 2018) - Pellicer, José Antonio; Rodríguez-López, María Isabel; Fortea, María Isabel; Gabaldón Hernández, José Antonio; Lucas-Abellán, Carmen; Mercader-Ros, María Teresa; Serrano-Martínez, Ana; Núñez-Delicado, Estrella; Cosma, Pinalysa; Fini, Paola; Franco, Esther; García, Rocío; et al.
Abstract: The adsorption properties of two cyclodextrin-epichlorohydrin polymers to remove Direct Red 83:1 textile dye from wastewater solutions was evaluated. Adsorption studies were performed in a batch reactor, and the efficiency of the polymers under different parametric values such as contact time, adsorbent dosage, initial dye concentration, pH of initial solution and temperature was followed by spectrophotometry. Both Langmuir and Freundlich equations were used to fit the equilibrium isotherms and the kinetic data were analyzed by the pseudo-first-order and pseudo-second-order models. Adsorption process follows a pseudo-second-order kinetic and was influenced by intraparticle diffusion model, dye concentration and contact time, reaching equilibrium within the first 30 min. Experimental data were better fitted to Freundlich isotherm model than to Langmuir and Temkin isotherms. Since about 93% of dye removal was achieved under optimized conditions, the α-cyclodextrin-epichlorohydrin polymer seems to be a useful device for removing Direct Red 83:1 from aqueous solutions and industrial effluents. Highlights: The adsorption of Direct Red 83:1 was performed using cyclodextrin polymers. The adsorption capacity was higher (93%) for α-CDs polymer. The adsorption kinetics was controlled by pseudo second order model. Freundlich isotherm presented the best fit to the experimental data.